Density functional theory investigations of structural, electronic and optical properties of III arsenides - Anua, Nurul Najwa (2014)
III arsenide semiconductor materials have attracted considerable attention because of their unique characteristics and unfailing applications as base materials in optoelectronics and many other state of the art technologies. In this study, III arsenide investigations are presented by performing calculations using computational approach framed within the density functional theory. Exchange-correlation energy functional plays a crucial role in the efficiency of density functional theory calculations, more soundly in the calculation of fundamental electronic energy band gap. In this density functional-theory study of III arsenide, the implications of exchange-correlation energy functional and corresponding potential were investigated on the structural, electronic and optical properties of III arsenides. For structural properties, local density approximation, generalized gradient approximation and parameterized generalized gradient approximation were applied. For the calculations of electronic properties, recently developed Tran-Blaha modified Becke-Johnson potential has been implemented additionally. To execute this study, state of the art computational code WIEN2k, based on full potential linearized augmented plane-wave and local orbitals methodology, was applied. III arsenide were simulated to obtain their lattice constant, band gap, dielectric constant, reflectivity, absorption, refraction index and the energy loss values. The results point to parameterized generalized gradient approximation as a more appropriate approximation for the calculations of structural parameters. However, the electronic band structure calculations at the level of modified Becke-Johnson potential showed considerable improvements over the other exchange correlation functionals. Besides this, the reported results related to optical properties within modified Becke-Johnson potential show a good agreement with the experimental measurements in addition to other theoretically results.